2007
DOI: 10.1192/bjp.bp.106.022954
|View full text |Cite
|
Sign up to set email alerts
|

Competition for neuronal resources: how hallucinations make themselves heard

Abstract: This finding indicates competition between auditory stimuli and hallucinations for physiological resources in the primary auditory cortex. The abnormal activation of the primary auditory cortex may thus be a constituent of auditory hallucinations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
61
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 85 publications
(69 citation statements)
references
References 39 publications
8
61
0
Order By: Relevance
“…In an early functional magnetic resonance imaging (fMRI) study we showed that the cerebral activity in the primary auditory cortex during the experience of internal voices is comparable to the activation caused by external auditory stimuli [14]. We propose that this dysfunctional activity may account for the belief of externality of the voices the patients hear, which may be further supported by the measurement of auditory evoked potentials in EEG, where we found higher EEG activity in left temporal regions and lower AEP amplitudes during AVH compared to phases without AVH [15].…”
Section: Introductionsupporting
confidence: 70%
See 2 more Smart Citations
“…In an early functional magnetic resonance imaging (fMRI) study we showed that the cerebral activity in the primary auditory cortex during the experience of internal voices is comparable to the activation caused by external auditory stimuli [14]. We propose that this dysfunctional activity may account for the belief of externality of the voices the patients hear, which may be further supported by the measurement of auditory evoked potentials in EEG, where we found higher EEG activity in left temporal regions and lower AEP amplitudes during AVH compared to phases without AVH [15].…”
Section: Introductionsupporting
confidence: 70%
“…Inversely, to guarantee the functional activity focus to be within the MRS ROI, one would have to increase the voxel size considerably, which would come with an enormous dilution effect with areas of different function and also with more white matter. However, the current study could not statistically test the difference between neurochemical results in functionally defined language regions (Broca"s area and Wernicke"s area) versus 15 those that could have been obtained in the corresponding regions defined by anatomical landmarks since this would have substantially prolonged the study procedure in a population of particularly vulnerable patients with limited resilience and compliance. The spectral quality was quite good for all spectra and ROIs, even though one ROI (Broca"s) was in a frontal location that is known to show significant B 0 field inhomogeneities.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…However, one common problem in the research of AVH is their fleeting nature, that is, AVH are dynamic on a minutes or subminutes time scale. This dynamic has been studied in fMRI [5,11,21] and electroencephalography (EEG) studies [13] to investigate neurophysiological changes even at the subsecond level [14].…”
Section: Neuroimaging and Electroencephalography (Eeg) Of Avhmentioning
confidence: 99%
“…Thus, AVH arise from a disorder of inner speech and its monitoring [17]. Altered activation in speech production areas (i.e., inferior frontal gyrus) and altered coupling with monitoring areas (anterior cingulate) and language reception areas (Wernicke's area) have been proposed in a model of bottom-up dysfunction through over-activation in secondary (and occasionally primary) sensory cortices that lead to the experience of vivid perceptions in the absence of sensory stimuli [12,13]. On the phenomenological level, the consequence of all this is the patient's unability to differentiate self-generated thoughts from external stimulation.…”
Section: Neuroimaging and Electroencephalography (Eeg) Of Avhmentioning
confidence: 99%